Estimation of Uneven Development of Lithuanian Regions - Cibulskiene, Diana; Butkus, Mindaugas; Matuzeviciūtė, Kristina (Ekonomika, 2005)
The researchers have aimed to analyse the processes of divergent development of Lithuanian regions by estimating the basic parameters of the process of interregional stratification. We have carried out an estimation of the process of differentiation using three parameters: per capita gross regional product (further GRP), per worker GRP and per capita foreign direct investment (further FDI) in a separate region. Using these indicators and the economic classical con vergence-divergence approaches of analysis, the principal dimensions of the unequal development of territorial units in Lithuania have been assessed.